Describing the Potential Crossreactome between Mumps Virus and Spermatogenesis-Associated Proteins - Kanduc, Darja (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2014)
This study documents that mumps virus shares several peptide sequences with human proteins that, when altered, may be involved in oligospermia/azoospermia, sterility and testicular atrophy. Examples are sperm flagellar protein 2 and spermatogenesis and centriole-associated protein 1. The data invite to further investigate crossreactivity as a potential mechanism linking anti-mumps immune responses, alterations of spermatogenesis–associated antigens and male fertility disorders.
Keywords: sterility